FACTORS AFFECTING CASH HOLDING MODERATED BY FIRM SIZE IN NON-CYCLICALS SECTOR COMPANIES - Aurelia, Ophilia; Wirianata, Henny (International Journal of Application on Economics and Business, 2025)
Cash holding is an important aspect in order to ensure the financial stability of a company. An excessive or insufficient amount of cash holding can lead to financial problems and disrupt the stability of a company. Therefore, it is essential for a company to maintain its level of cash holding in an optimal level. This research seeks to explore the influence of profitability, liquidity, net working capital, capital expenditure, also firm size on cash holding considering the moderating role of firm size in consumer non-cyclicals firms registered on Indonesia Stock Exchange (IDX) from 2021-2023 period. Secondary financial data is employed and chosen through purposive sampling method. Data were processed using Microsoft Excel 2021 and tested using Eviews version 12. The outcomes determined that profitability, liquidity, as well as firm size positively impacts cash holding. Meanwhile, it is discovered that a inverse relationship exists among net working capital and cash holding, and capital expenditure does not impact cash reserves of a company. The moderation test analysis in this study imply that size of a firm is qualified in moderating the impact of profitability and net working capital in determining cash reserves. Conversely, size of a firm does not have the capacity in moderating the influence of liquidity and capital expenditure in determing cash holding.